2007
DOI: 10.1111/j.1460-9568.2007.05499.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Kir6.2‐containing ATP‐sensitive potassium channels impairs maintenance of hypoxic gasping in mice

Abstract: Hypoxic gasping emerges under severe hypoxia/ischemia in various species, exerting a life-protective role by assuring minimum ventilation even in loss of consciousness. However, the molecular basis of its generation and maintenance is not well understood. Here we found that mice lacking Kir6.2- but not Kir6.1-containing ATP-sensitive potassium (K(ATP)) channels [knockout (KO) mice] exhibited few gaSPS when subjected to abrupt ischemia by decapitation, whereas wild-type mice all exhibited more than 10 gaSPS. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…It was reported that respiratory activity monitoring by a similar PZT sensor was in good agreement with that by a CO 2 respiratory monitor [24] or a thermistor airflow sensor [7] in mice. However, a large deformation of respiratory signal due to motion artifacts, routine care and artificial ventilation made BR evaluation impossible in about 30% of the total recording time in the present study ( table 3 ).…”
Section: Discussionmentioning
confidence: 54%
“…It was reported that respiratory activity monitoring by a similar PZT sensor was in good agreement with that by a CO 2 respiratory monitor [24] or a thermistor airflow sensor [7] in mice. However, a large deformation of respiratory signal due to motion artifacts, routine care and artificial ventilation made BR evaluation impossible in about 30% of the total recording time in the present study ( table 3 ).…”
Section: Discussionmentioning
confidence: 54%
“…Recently, it was shown that a transgenic mouse lacking the K + channel responsible for the ATP‐sensitive K + current exhibited an exacerbated initial augmentation, along with a weaker secondary depression, in response to hypoxia 60 . In a similar report, using another mouse lacking ATP‐sensitive K + currents, it was found that those animals exhibited an exacerbated initial augmentation along with shortened duration of gasping rhythm generation 61 …”
Section: Respiratory Network Changes During the Generation Of Gaspingmentioning
confidence: 92%
“…These include apamin-sensitive SK3 potassium channels (34), neuronal ATP-sensitive potassium (K ATP ) channels formed by Kir6.2 (343, 353) and SUR1 subunits (4, 230), and pH-sensitive inward rectifier (Kir2.2; 387) and “two-pore” potassium channels [TASK1, TASK3; (363); TASK2, (172)]. In general, none of these genetic manipulations of single potassium channel genes yielded overtly catastrophic respiratory phenotypes, as all strains were viable, even if mutant phenotypes were observed in the context of isolated preBötC slices or single neuronal recordings.…”
Section: Potassium Currents and Their Contribution To Respiratory Rhymentioning
confidence: 99%
“…The role for K ATP channels was also examined at the behavioral level using a mouse strain in which Kir6.2 was genetically deleted (353, 386). Deletion of Kir6.2 was found to clearly abolish the gasping response induced by decapitation.…”
Section: Cellular Properties and The Integration Of Central Chemosensmentioning
confidence: 99%